Antioxidant Activity of Polysaccharides from the Edible Mushroom Pleurotus eryngii - Tania Petraglia; Tiziana Latronico; Angela Fanigliulo; Aniello Crescenzi; Grazia Maria Liuzzi; Rocco Rossano (Molecules, 2023)
In this study the antioxidant and neuroprotective activity of an enriched polysaccharide fraction (EPF) obtained from the fruiting body of cultivated P. eryngii was evaluated. Proximate composition (moisture, proteins, fat, carbohydrates and ash) was determined using the AOAC procedures. The EPF was extracted by using, in sequence, hot water and alkaline extractions followed by deproteinization and precipitation with cold ethanol. Total α- and β-glucans were quantified using the Megazyme International Kit. The results showed that this procedure allows a high yield of polysaccharides with a higher content of (1-3; 1-6)-β-D-glucans. The antioxidant activity of EPF was detected from the total reducing power, DPPH, superoxide, hydroxyl and nitric oxide radical scavenging activities. The EPF was found to scavenge DPPH, superoxide, hydroxyl and nitric oxide radicals with a IC50 values of 0.52 ± 0.02, 1.15 ± 0.09, 0.89 ± 0.04 and 2.83 ± 0.16 mg/mL, respectively. As assessed by the MTT assay, the EPF was biocompatible for DI-TNC1 cells in the range of 0.006–1 mg/mL and, at concentrations ranging from 0.05 to 0.2 mg/mL, significantly counteracted H2O2-induced reactive oxygen species production. This study demonstrated that polysaccharides extracted from P. eryngii might be used as functional food to potentiate the antioxidant defenses and to reduce oxidative stress.